Design on non-stop transportation plugging device for subsea pipeline. Issue 1 (July 2021) - Jiang, Hao; Meng, Lingzhi; Niu, Xuebin; Zhang, Lijun; Wang, Longting; Li, Dawei; Xu, Wenkai; Zhang, Binghui
Abstract: The process of plugging with pressure outside the subsea pipeline is cumbersome. The common technology cannot transport oil and gas during the maintenance process, and a new type of subsea pipeline non-stop transportation plugging technology is proposed. In this paper, an oil and gas pipeline with a diameter of 324mm and a pressure of 3MPa is taken as the research object for overall design and feasibility analysis. The anchoring and sealing performance of the packer is calculated, checked and analyzed using the element method. The results indicated that the plugging device can meet the plugging requirements of non-stop transportation of subsea oil and gas pipelines in maintenance.